Unusual Presentations of Sellar and Suprasellar Space Occupying Lesion: Our Institutional Experience - Ramalingam Giridharan; Nirmal Kumar; J. Srisaravanan (Indian Journal of Neurosurgery)
A pituitary abscess (PA) is a rare intracranial lesion. It is a critical disorder caused by an infectious process where purulent material accumulates inside the sella turcica. It occurs either as a primary disease or because of an infection and is associated with poor prognosis. In this article, we share our experience with PA. At our institution, we operated on five cases of pituitary abscess since 2016. All the cases presented with bitemporal hemianopia and headache. None of them had fever. Pituitary hormones were normal except in two patients with a previous history of hypothyroidism. Magnetic resonance imaging (MRI) of the brain showed pituitary macroadenoma. They underwent the endoscopic transnasal transsphenoidal approach. Postoperatively their vision has improved. Endocrine functions were normal in all the patients following surgery. Culture sensitivity was sterile in all the patients. Diagnosis of pituitary abscess is highly difficult before surgery. Hence, the diagnosis should be considered when a patient presents with fever, headache, and signs of pituitary dysfunction and meningeal inflammation. Surgical and medical management leads to a lower mortality rate and a higher probability of hormone function recovery.